Elevated red cell distribution width predicts residual dizziness in patients with benign paroxysmal positional vertigo - Xie, Ke-Hang; Chen, Li-Chun; Liu, Ling-Ling; Su, Chu-Yin; Li, Hua; Liu, Run-Ni; Chen, Qing-Qing; He, Jia-Sheng; Ruan, Yong-Kun; He, Wang-Kai (Frontiers in Neurology, 2022)
Objective The present study aimed to determine whether residual dizziness (RD) after successful repositioning treatment in benign paroxysmal positional vertigo (BPPV) patients could be predicted by red blood cell distribution width (RDW). Materials and methods In this study, a total of 303 BBPV patients hospitalized at the neurology department were investigated. The enrolled patients were divided into two groups after successful repositioning treatment: non-RD group included patients who were completely cured, and RD group included patients with RD. We collected data on all subjects, including general information, blood routine examination, blood biochemical examination, and magnetic resonance imaging tests. Results The mean RDW values of patients in the RD group were significantly higher than that in the non-RD group (13.63 ± 1.8 vs. 12.5 ± 0.8; p < 0.001). In subsequent multivariate analysis, elevated RDW levels were a statistically significant risk factor associated with the occurrence of RD [odds ratio = 2.62, 95% confidence interval (CI) 1.88–3.64, p < 0.001]. The area under the ROC curve was 0.723 in terms of its predictive ability to distinguish patients with RD. A cut-off point of 12.95% of RDW predicted RD with a sensitivity of 75.6% and a specificity of 69.5%. Moreover, the AUC for the ability of the RDW to predict recurrence were 0.692 (95% CI = 0.561–0.831; p < 0.014). Conclusions Elevated RDW level was related to increased risk of RD among BPPV patients, requiring further efforts to clarify the actual underlying pathophysiology.